2021
DOI: 10.1161/circulationaha.121.054302
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin Thresholds and Kinetics to Differentiate Myocardial Injury and Myocardial Infarction

Abstract: Background: Whilst the 99th percentile is the recommended diagnostic threshold for myocardial infarction, some guidelines also advocate the use of higher troponin thresholds to rule-in myocardial infarction at presentation. It is unclear whether the magnitude or change in troponin concentration can differentiate causes of myocardial injury and infarction in practice. Methods: In a secondary analysis of a multi-centre randomized controlled trial, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 56 publications
(125 reference statements)
1
29
1
Order By: Relevance
“…Second, although performance of the low-probability threshold was consistent across important patient subgroups, we observed heterogeneity in the PPV of the high-probability threshold, particularly when stratified according to the primary presenting symptom. This finding is consistent with our previous research 29 , 30 and probably reflects the greater prevalence of non-ischaemic myocardial injury and type 2 myocardial infarction in our consecutive patient population as compared with the cohorts used to train the algorithm whereby some patient selection was inevitable. It is possible that an algorithm that incorporates other clinical features might perform more consistently across these subgroups when identifying patients at high probability of type 1 myocardial infarction.…”
Section: Discussionsupporting
confidence: 92%
“…Second, although performance of the low-probability threshold was consistent across important patient subgroups, we observed heterogeneity in the PPV of the high-probability threshold, particularly when stratified according to the primary presenting symptom. This finding is consistent with our previous research 29 , 30 and probably reflects the greater prevalence of non-ischaemic myocardial injury and type 2 myocardial infarction in our consecutive patient population as compared with the cohorts used to train the algorithm whereby some patient selection was inevitable. It is possible that an algorithm that incorporates other clinical features might perform more consistently across these subgroups when identifying patients at high probability of type 1 myocardial infarction.…”
Section: Discussionsupporting
confidence: 92%
“…First, the magnitude of hs-cTnT release appeared to be similar as in type 1 NSTEMI. This contrasts to data reported elsewhere [3] , [4] , [5] and likely depends on the exclusion of patients with ST-elevation MI from our cohort. Even differences in blood sampling strategies may have contributed.…”
Section: Discussioncontrasting
confidence: 91%
“…Our data however, also highlight the difficulties to distinguish type 2 from type 1 NSTEMI, and hs-cTnT concentrations provide no clue in this regard. Even previous data demonstrated that cTn only provides limited discriminative value [4] , [5] , [8] , [9] . Some studies have suggested that this could be enhanced by the consideration of clinical findings and/or other biomarkers [10] , [11] , [12] , [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, cTns continue to represent the gold standard for MI diagnosis. However, even if they are still among the most widely used cardiac biomarkers, their low positive predictive power and low disease specificity can lead to incorrect diagnosis, as they are not completely specific to MI [8][9][10]. Additionally, the improved sensitivity of high analysis assay cTns (hs-Tns) is associated with prolonged time to correct diagnosis, undue interventions, and has diminished value in the first era of disease development, and its prognostic role is less well-established.…”
Section: Introductionmentioning
confidence: 99%